A systematic review of non-functional requirements mapping into architectural styles - Muhammad Nouman; Muhammad Azam; Ashraf Mousa Saleh; Abdullah Alsaeedi; Hayfa Yousef Abuaddous (Institute of Advanced Engineering and Science, 2023)
Fortunately, the software attracted enough businesses to the market, allowing them to earn money in less time with less work and more accurate results. Software development life cycle (SDLC) is used for software development as it is responsible for system functionality, efficiency, maintainability, and any other non-functional system requirements. Each stage of the SDLC process is critical. However, software requirements and software architecture are both fundamental activities that play a vital role in all other SDLC stages. Non-functional requirements are critical to the success of any software because they explain all system quality attributes such as complexity, reliability, security, and maintainability, among others. The architectural styles assist you in determining which architecture may be best for your project requirements. This paper discusses several of the most important architectural styles that are best suited for mapping desired non-functional requirements for software development, as well as their comparison based on various quality attributes (non-functional requirements).